SURVEY ON SPORTS INJURIES SURABAYA FEMALE VOLLEYBALL PLAYERS - WIDYATI, DINI (Jurnal Prestasi Olahraga, 2013)
A volleyball player is certainly not injury. Injuries that are volleyball players are muscles, tendons, ligaments and joints. Injuries treatment by massaging and withdrawal in areas such as injury strain injuries, sprains, fractures, and dislocations (bone shift), while the injured were treated by medicine serve or with the alternative treatment. This study aims to determine subjec about injuries and of women volleyball players Surabaya. Subjec players this research is Surabaya women volleyball players who totaled 50 players. Methods of data collection in this study using a questionnaire. The conclusion research: 1) injured as many as 32 ??people or 64% of the total of 50 women volleyball players. 2) Handling injuries women players volleyball is help to women volleyball players a coach as many as 23 people or 46% of the total of 50 players, to the injury of the medical team that is currently using as many as 16 people or 32 50% of players, and severe injuries as many as 26 people or 52% of the total of 50 players. Keywords: Survey, Injury, volleyball.